Azerbaijan Republic : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2003)
This paper reviews Azerbaijan's State Program on Poverty Reduction and Economic Development 2003-2005 (SPPRED). The Poverty Reduction Program in Azerbaijan has attracted an extensive and high degree of interest, matching its complexity and scope. The main objective of the SPPRED is to define and measure poverty in Azerbaijan using a variety of indicators, identify the causes of poverty, and develop a strategy to address these causes. The role of a participatory dimension in the SPPRED is to ensure a comprehensive and genuine process of consultation with the civil society.